TR2 Can augmented reality improve the simulation experience?. (November 2018) - Judd, Thomas; Young, Alexander
Abstract : Background: With technological advances in virtual reality (VR) it is now possible to deliver totally immersive VR scenarios via a smartphone. This has the benefit of addressing the cost issues of high-fidelity simulators and the number of faculty required to run simulations. VR also addresses the visual issue that plastic SIM manikins do not react like real patients, e.g. with a change in skin colour from hypoxia1. However, virtual reality loses the SIM manikin's advantage of giving tactile feedback, e.g. in cardio-pulmonary resuscitation. Augmented reality (AR) can combine the two concepts of high fidelity simulation and VR, to give the best of both worlds. It does so by overlaying an image onto a low fidelity manikin which then looks like a real patient when viewed through a head set. The use of avatars in AR reduces the need for additional faculty, as pre-programmed AR scenarios can run independently without the need for tutor involvement. Furthermore, AR can be used on top of a simulator manikin to enhance tactile feedback. This technology can improve accessibility to learning opportunities, as it removes the limitations of faculty and simulation space. Summary of project: Run a randomised control trial to assess AR scenarios compared to a high fidelity simulation manikin when teaching medical students about medical emergencies. The students will be randomised to the AR teaching or simulation manikin teaching session. Following the teaching session students will fill out a questionnaire about their teaching experience. The students will then be assessed on the learning outcome session by sitting a simulation assessment on a high fidelity manikin and a MCQ test. Quantitive outcome measures will be comparing the students' performance on the MCQ test. As well as measuring time to carry out key events during the simulation. Qualitative outcomes will be measured using the student questionnaire, which will assess student engagement, enjoyment, and preparedness for clinical practice. The questionnaire will use a Likert scale to measure student responses. Summary of results: The AR app is still under development with a number of scenarios being programmed on to the platform. However, our hypothesis is that AR technology will improve enjoyment and engagement in simulation teaching as well as improved performance Discussion and conclusion: Once the app has been fully developed and tested on clinical educators it will be ready to use in a trial. The aim is to start the study at beginning of September 2018.